Družbeni akterji in slovenska kulturna identiteta v medijskem diskurzu dveh obdobij - Bergoč, Simona (Jezik in slovstvo, 2008)
The article presents research on the social actors who were linked with notions of national culture, and either directly or indirectly also with national language, in the context of two major political upheavals of Slovene nation forming: the period before the plebiscite for secession from the multilingual and multinational Yugoslavia (1990) and the period before the referendum for inclusion in the multilingual and multinational European Union (2003). The social actors are analysed quantitatively, in the sense of the number of their appearances - i.e., their lesser or greater presence in the field of public communication - as well as qualitatively, in the sense of their way of representation and the discursive effects that their specific ways of articulation evoke. The research demonstrates the participatory circumstances of declaring and taking issue with cultural-identity questions and the operation of the ideology of linguistic exclusivity in the context of wide-ranging political decisions.
Keywords: communication medium; communication sciences; komunikologija; kulturna identiteta; mediji; medijski diskurz; politics; politika; Slovene; slovenščina; sociolinguistics; sociolingvistika